Entrepreneurial ecosystem and well-being in European smart cities: a comparative perspective. Issue 7 (5th October 2021) - Penco, Lara; Ivaldi, Enrico; Ciacci, Andrea
Abstract : Purpose: This study investigates the relationship between the strength of innovative entrepreneurial ecosystems and subjective well-being in 43 European smart cities. Subjective well-being is operationalized by a Quality of Life (QOL) survey that references the level of multidimensional satisfaction or happiness expressed by residents at the city level. The entrepreneurial ecosystem concept depicted here highlights actor interdependence that creates new value in a specific community by undertaking innovative entrepreneurial activities. The research uses objective and subjective variables to analyze the relationships between the entrepreneurial ecosystem and subjective well-being. Design/methodology/approach: The authors conducted a cluster analysis with a nonaggregative quantitative approach based on the theory of the partially ordered set (poset); the objective was to find significant smart city level relationships between the entrepreneurial ecosystem and subjective well-being. Findings: The strength of the entrepreneurial ecosystem is positively related to subjective well-being only in large cities. This result confirms a strong interdependency between the creation of innovative entrepreneurial activities and subjective well-being in large cities. The smart cities QOL dimensions showing higher correlations with the entrepreneurial ecosystem include urban welfare, economic well-being and environmental quality, such as information and communications technology (ICT) and mobility. Practical implications: Despite the main implications being properly referred to large cities, the governments of smart cities should encourage and promote programs to improve citizens' subjective well-being and to create a conducive entrepreneurship environment. Originality/value: This study is one of the few contributions focused on the relationship between the entrepreneurial smart city ecosystem and subjective well-being in the urban environment.